Peran Analisis Podcast Terhadap Media Pembelajaran Digital Mahasiswa di Era Milenial - Sariski, Aldo; Tanjung, Salsas Bila Juniyanti; Nirwana, Rena Putri; Julio, Christopher Elia; Nandita, Lufna; Rasyad, Pasha Athallah; Hibatullah, Abdurrafi; Handhani, Muhammad Gading Bintang; Tambunan, Daniel; Herley, Airiique Bintang Merah; Zulfikar, Faiz Raudhin; S, Subakdi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of digital technology in the millennial era has revolutionized the way students obtain and process information, especially in the context of higher education. Podcasts, as an audio-based digital learning medium, offer flexibility, accessibility and special appeal for the younger generation who are familiar with digital content. This article analyzes the role of podcasts as a legal learning medium with a case study of three episodes of the "Mata Najwa" podcast which discuss legal issues, especially corruption cases and the justice system in Indonesia. This research uses a qualitative approach with a content analysis method, which focuses on the cognitive, affective and conative aspects of students after watching the show. The research results show that podcasts not only increase legal understanding (cognitive), but also build empathy (affective), and trigger active participation of students as agents of change (conative). Inspirational narratives and relevant content in podcasts have proven effective in building legal awareness, integrity, and student motivation to get involved in social issues. However, the use of podcasts as an educational medium also faces regulatory challenges, digital literacy, and the risk of spreading inaccurate information. With proper management and adequate policy support, podcasts can be a transformative learning strategy in the era of digital education.